Since Meiji : perspectives on the Japanese visual arts, 1868-2000 - McCallum, Toshiko M. (Toshiko Miyabayashi), 1943-; Rimer, J. Thomas (University of Hawaiʻi Press, 2011)
Research outside Japan on the history and significance of the Japanese visual arts since the beginning of the Meiji period (1868) has been, with the exception of writings on modern and contemporary woodblock prints, a relatively unexplored area of inquiry. In recent years, however, the subject has begun to attract wide interest. As is evident from this volume, this period of roughly a century and a half produced an outpouring of art created in a bewildering number of genres and spanning a wide range of aims and accomplishments. Since Meiji is the first sustained effort in English to discuss in any depth a time when Japan, eager to join in the larger cultural developments in Europe and the U.S., went through a visual revolution. Indeed, this study of the visual arts of the nineteenth and twentieth centuries suggests a fresh history of modern Japanese culture--one that until now has not been widely visible or thoroughly analyzed outside that country. In this extensive collection, which includes some 190 black-and-white and color reproductions, scholars from Japan, Europe, Australia, and America explore an impressive array of subjects: painting, sculpture, prints, fashion design, crafts, and gardens. The works discussed range from early Meiji attempts to create art that referenced Western styles to postwar and contemporary avant-garde experiments. There are, in addition, substantive investigations of the cultural and intellectual background that helped stimulate the creation of new and shifting art forms, including essays on the invention of a modern artistic vocabulary in the Japanese language and the history of art criticism in Japan, as well as an extensive account of the career and significance of perhaps the best-known Japanese figure concerned with the visual arts of his period, Okakura Tenshin (1862-1913), whose Book of Tea is still widely read today. Taken together, the essays in this volume allow readers to connect ideas and images, thus bringing to light larger trends in the Japanese visual arts that have made possible the vitality, range, and striking achievements created during this turbulent and lively period.